The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.5761/atcs.oa.20-00029
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Minimally Invasive Thoracoscopic Left Atrial Appendage Excision on Cardiac Dynamic and Endocrine Function

Abstract: Purpose: Left atrial appendage (LAA) isolation is an effective surgical treatment for decreasing thromboembolic risk. We sought to evaluate the short-term effect of minimally invasive surgery with LAA excision on left atrial dynamic and endocrine function in atrial fibrillation (AF) patients. Methods: A total of 52 patients with paroxysmal AF undergoing minimally invasive surgery with LAA excision in Anzhen Hospital from October 2012 to June 2014 were enrolled in the study. The natriuretic peptide p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…the average serum sodium level decreased by 5.65 ± 2.61 mmol/L within 48 hours postprocedure, and there were 13 patients (61.9%) who decreased ≥ 4mmol/L, and 3 patients (14.29%) decreased ≥ 10 mmol/L. As a common postoperative complication, hyponatremia could induce severe central nervous system dysfunction including headache, nausea, lethargy, disorientation, or depressed re exes 20 .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…the average serum sodium level decreased by 5.65 ± 2.61 mmol/L within 48 hours postprocedure, and there were 13 patients (61.9%) who decreased ≥ 4mmol/L, and 3 patients (14.29%) decreased ≥ 10 mmol/L. As a common postoperative complication, hyponatremia could induce severe central nervous system dysfunction including headache, nausea, lethargy, disorientation, or depressed re exes 20 .…”
Section: Discussionmentioning
confidence: 98%
“…Additionally, the cerebral edema induced by rapid and signi cant uctuations in serum sodium levels can lead to serious complications including seizures, coma, brain damage, and brain-stem herniation due to cerebral edema 20 . The predictable decline of serum sodium, we observed, secondary to the stand-alone thoracoscopic left atrial appendage clipping, could elucidate the early, unexplained postoperative serum sodium decline and may obviate further expensive and unnecessary investigation.…”
Section: Discussionmentioning
confidence: 99%
“…These concentrations may or may not return to preprocedural level. Interestingly, in a recent study where LAA was surgically excised in 52 patients, plasma ANP levels were almost the same at 3 time points: preprocedure, 7 days and 3 months after procedure [9 ▪ ]. The discordancy between studies might be attributed to the different time points at which blood samples were collected.…”
Section: Introductionmentioning
confidence: 94%
“…In the following 30–45 days after LAAE, it seemed that LA would self-adjust in response to the modification of loading condition. Following LAA excision, changes in the LA size and function were similar: maximum LA volume and LA empty fraction significantly decreased 7 days after the procedure but returned to the preprocedural level in 3 months [9 ▪ ]. Two studies, both used 2D speckle tracking imaging technique, have shown that LA reservoir function improved at short-term follow-up after LAA closure [36,37].…”
Section: Introductionmentioning
confidence: 94%
“…Two small studies indicated a slight rise in brain natriuretic peptide levels after transcatheter LAAO (32 patients together) [47,48]. On the other hand, there are several studies demonstrating that LAAO does not lead to any significant changes in natriuretic peptide levels at all [43,[49][50][51][52]. For instance, the abovementioned prospective randomized study PRAGUE-17 (400 patients) did not observe a difference in levels of natriuretic peptides between the LAAO and anticoagulated groups [53].…”
Section: Collateral Impact Of Laa Lossmentioning
confidence: 99%